How to do things with words - Austin, J. L. (London Oxford university press, 1955)
John L. Austin was one of the leading philosophers of the twentieth century. The William James Lectures presented Austin's conclusions in the field to which he directed his main efforts on a wide variety of philosophical problems. These talks became the classic How to Do Things with Words.For this second edition, the editors have returned to Austin's original lecture notes, amending the printed text where it seemed necessary. Students will find the new text clearer, and, at the same time, more faithful to the actual lectures. An appendix contains literal transcriptions of a number of marginal notes made by Austin but not included in the text. Comparison of the text with these annotations provides new dimensions to the study of Austin's work